2017
DOI: 10.1128/aac.00280-17
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Assessment of Vancomycin Loading Dose in Critically Ill Patients

Abstract: The vancomycin loading dose (LD) of 25 to 30 mg/kg is a frequently practiced strategy to achieve effective concentrations from the first-treatment dose. However, considering only the body weight for dosing might be inadequate in critically ill patients due to pharmacokinetics changes. We sought to assess achieving optimal trough serum levels of vancomycin and AUC 0 -24 /MIC in the first 24 h of treatment by using an LD based on population pharmacokinetic parameters of critically ill patients. We performed a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 36 publications
0
30
0
1
Order By: Relevance
“…Our results showed that the current daily dose was too low for all neonatal age groups but particularly for neonates <29 weeks, as less than 30% of neonates reached the steady-state target. As a loading dose strategy is recommended in adult settings in order to reduce the time needed to reach the target AUC0-24 47,48 simulations were then performed with a loading dose and optimal maintenance doses in all age groups, based on weight and PMA. Increasing the maintenance dose to 15 mg/kg 'q12h' instead of 'q24h' was also tested in the group <29 PMA weeks to optimise dosage.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the current daily dose was too low for all neonatal age groups but particularly for neonates <29 weeks, as less than 30% of neonates reached the steady-state target. As a loading dose strategy is recommended in adult settings in order to reduce the time needed to reach the target AUC0-24 47,48 simulations were then performed with a loading dose and optimal maintenance doses in all age groups, based on weight and PMA. Increasing the maintenance dose to 15 mg/kg 'q12h' instead of 'q24h' was also tested in the group <29 PMA weeks to optimise dosage.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain a high concentration thereafter, an increase in the maintenance dose from 15 mg/kg to 20 mg/kg might be required [22]. Many studies reported a higher achievement of a C min >15 μg/mL after the first dose in patients with a loading dose compared with patients without a loading dose [10,15,23,24]. Casapao et al [25] evaluated the association between the day 1 vancomycin exposure profile and outcomes among patients with MRSA infective endocarditis, and an AUC/MIC of < 600 was independently associated with failure.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians, however, tend to be reluctant to use a loading dose, especially in patients with decreased renal function, for fear of causing renal injury. Alvarez et al [10] demonstrated that all patients with a loading dose who presented with decreased vancomycin clearance before the administration of vancomycin had an elevated serum concentration (>28 μg/mL) in the first 24 h of treatment. These patients, however, did not have nephrotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus ( S. aureus ) , known as one of the most frequent strain usually causes food poisoning and widespread infection, and is a risk factor for exacerbating HAPUs. It comes from superficial skin and other soft tissue infections to life threatening toxic shock, skeletal system, circulatory system, respiratory system, implantable medical devices, and the blood stream 4-6. At present, S. aureus -associated HAPUs have been increasing year by year.…”
Section: Introductionmentioning
confidence: 99%